Sprawozdanie z działalności Zarządu Stowarzyszenia Teologów Moralistów w Polsce za lata 2019-2022 - Derdziuk, Andrzej (Teologia i Moralność, 2022)
The text discusses three years of activity of the Association of Moral Theologians in Poland. It points out the annual scientific meetings and other forms of scientific activity of the Association's members.